CREATION OF THE SERVICE CONTENT OF THE PEDAGOGICAL EDUCATION CLUSTER (on the example of the city of Chirchik) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The regional educational cluster introduced in the Tashkent region is a single mobile technological cooperation of educational types as the most convenient means of accepting optimal solutions quickly and easily, affecting the cohesion between educational subjects, ensuring social order. information field - showed the need to create an open educational content (services platform) of the pedagogical education cluster, the problems, goals and tasks and importance of this issue are justified in this article.